2018
DOI: 10.24093/awej/vol9no2.1
|View full text |Cite
|
Sign up to set email alerts
|

Minding the Gap in Vocabulary Knowledge: Incidental Focus on Collocation through Reading

Abstract: The present study seeks to contribute to our knowledge of the effectiveness of reading in the incidental learning of collocations. The study also addresses the question whether out-of-class exposure such as watching TV, listening to radio or music, reading English books and using social media plays a significant role in the learning of collocations. The research participants were 46 Arabic-speaking young adult EFL learners. They were asked to read a modified text containing 10 pseudo-word collocations and to v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Clearly in the current study, the presence of context was advantageous and able to strengthen the interpretation of the figurative collocations and led to overly impressive amount of learning, hence showed evidence of incidental collocation learning while reading. The results are in line with recent similar studies on the learning of collocation in classroom settings (Alharthi, 2018;Boers et al, 2014;Durrant & Schmitt, 2010;Sonbul and Schmitt, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Clearly in the current study, the presence of context was advantageous and able to strengthen the interpretation of the figurative collocations and led to overly impressive amount of learning, hence showed evidence of incidental collocation learning while reading. The results are in line with recent similar studies on the learning of collocation in classroom settings (Alharthi, 2018;Boers et al, 2014;Durrant & Schmitt, 2010;Sonbul and Schmitt, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…In the absence of intentional treatments, particularly in the context of EFL, it is observed that incidental learning of collocation might be most effective. Focusing on implicit collocation learning, Alharthi (2018) examined the degree of EFL learners' productive task of verb-noun combinations at three word frequency bands affected their knowledge of collocations while reading. The results showed that incidental learning of collocation suited to promote the development of productive knowledge and that the frequency of occurrence is more effective at fostering such development.…”
Section: Collocation Learning In Non-native Speakersmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, plenty of other research have found that language learners improve their vocabulary knowledge by accident as a result of intensive reading. This is backed by [5], who conducted a research at Saudi Arabia's King Abdulaziz University to see if students may learn collocations by being exposed to target text repeatedly. The quantitative study revealed the chosen respondents memorize the collocations by reading extensively.…”
Section: Introductionmentioning
confidence: 99%
“…The commonsense view of vocabulary assessment is to address this knowledge in the four separate skills, i.e., reading and listening (receptive skills) and writing and speaking (productive skills) (Fitzpatrick & Clenton, 2017). Many L2 vocabulary researchers have highlighted the potential relationship between vocabulary knowledge and the ability to read, write and listen in the target language (e.g., Alharthi, 2018Alharthi, , 2019Laufer & Aviad-Levitzky, 2017;Staehr, 2009;Wang & Treffers-Daller, 2017). With the exception of De Jong, Steinel, Florijn, Schoonen, and Hulstijn (2012), Koizumi and In'nami (2013), Milton, Wade, and Hopkins (2010) and Uchihara and Clenton (2018), it is almost certain that no study has attempted to examine the association between vocabulary knowledge and ability to speak in a Saudi setting.…”
Section: Introductionmentioning
confidence: 99%